Pengembangan E-LKPD menggunakan model problem-based learning pada materi statistika - Sumandya, Esa Aulia; Elvi, Mariyanti; Rosmery, Linda (Karoteh Utama, 2025)
This study was motivated by the low level of student engagement in mathematics learning and the limited use of textbooks in fostering problem-solving skills. Based on classroom observations and interviews with teachers and students of Grade VIII at SMP Negeri 12 Tanjungpinang, mathematics learning remained conventional and teacher-centered. Therefore, an electronic student worksheet (E-LKPD) based on the Problem Based Learning (PBL) model was developed for the Statistics topic. The aim of this research was to produce a PBL-based E-LKPD that is both valid and practical for classroom use. This research employed a Research and Development (R&D) approach using the ADDIE model, focusing on the analysis, design, and development stages. The research subjects consisted of one mathematics teacher and 33 students. The validation results showed that the material aspect achieved 86.60% (valid), while the media aspect reached 90.00% (highly valid). The practicality tests conducted with teachers and students yielded 90.00% and 90.91%, respectively, categorized as highly practical. Thus, the E-LKPD based on the Problem Based Learning model for the Statistics topic is considered valid, attractive, and effective to support learning activities.